Survei Investigasi Desain Dinding Penahan Tanah Kafe Panorama Karang Panjang, Kota Ambon (Studi Kasus) - Rudolf Bernard; Pieter Lourens Frans; Edison Hukom (Universitas Pahlawan Tuanku Tambusai, 2024)
A soil retaining wall is a construction built to withstand or support soil pressure and other lateral loads with the aim of preventing the soil from unwanted lateral movement. The function of utanabya is to maintain changes in elevation or slope of the soil and ensure slope stability. This study aims to determine soil parameters and design soil retaining walls according to standards or theories. From the results of laboratory tests and calculations of soil retaining walls, the soil around the Karang Panjang Panorama Cafe, Ambon City is clay sand soil and soil retaining walls are designed, namely cantilever type retaining walls using the rankine method with typical dimensions based on SNI 8460: 2017 standards with dimensions of top width of 0.3 meters, bottom width of 3.15 and height of 4.5 meters where the safety factor number against bolsters is 2.164 (safe) against shear 1,728 (safe).